"Flipgrid netiquette": unearthing language ideologies in the remote learning era. (3rd July 2021) - Bauler, Clara Vaz
ABSTRACT: Flipgrid as an asynchronous video-mediated online discussion platform has offered a space for teachers and students to interact and show their thinking in remote learning during the COVID-19 pandemic. While Flipgrid discussions can afford educators the chance to build on students' creative language use, the choices teachers make when designing the discussions can also perpetuate standard language ideologies and purist language norms. This study presents a critical analysis of free and available teaching materials designed to support the use of Flipgrid, highlighting examples that foster or constrain student language choice and body positioning according to socially constructed norms for "Flipgrid netiquette."